Impact of skills training on employment among young entrepreneurs in selected local governments in Ibadan, Nigeria (2019)
This study investigated the impact of skills training on employment among young entrepreneurs in selected Local Governments in Ibadan, Nigeria. There were three hundred and eighty-two young entrepreneurs in the Akinyele, Ibadan North and I do Local Government areas of Oyo State who responded to the questionnaires on the General Effectiveness Training Skills scale and Employability Appraisal Scale. The study was anchored on Dreyfus model of skill acquisition. Two hypotheses were tested for, using the t-test for independent sample t-test. The result shows that there was a significant difference in the ability of the participants to secure better jobs between participants with high skills training and low skills training, t (380) = 5.73, p< .05. The result also showed that participants with high skills training had the ability to secure better jobs than those with low skills training. There was no significant gender difference in the ability of the participants to secure better jobs. This study therefore, emphasizes the need for continuous skills training among the young entrepreneurs in the areas, to reduce the menace of poverty and in order to move away from being an an underdeveloped country to becoming a developed country; and that government at all levels must do all it con to improve the skills of young entrepreneurs